Ga ions-tailored magnetic-dielectric properties of Mg–Cd composites for high-frequency, miniature and wideband antennas. Issue 6 (15th April 2020) - Gan, Gongwen; Zhang, Dainan; Li, Jie; Wang, Gang; Huang, Xin; Rao, Yiheng; Yang, Yan; Wang, Xueying; Zhang, Huaiwu; Chen, Ray T.
Abstract: Mg ferrites are essential to stabilize the spinel structure of magnetic-dielectric composites. This study investigates the effect of Ga ions on the magnetic and dielectric properties and low-loss characteristics of Mg–Cd composites sintered at low temperature with the addition of 2.5 wt% Bi2 O3 . The variation in the Ga substitution of Fe at the octahedral site, with x increasing from 0.00 to 0.18 (Mg0.8 Cd0.2 Fe2-x Gax O4 ), increases magnetization, which plays the key role in determining the permeability. The real part of the permeability ( μ ′) of the Ga-substituted ferrites was reported to increase monotonically from 10 H/m to 56 H/m. Meanwhile, the real part of the permittivity ( ε ′) was optimized by the Ga ions. Consequently, relatively matching impedance factor (Z ≈ 1.34) and wideband characteristic factor ( BWR ≈ 2.5 × 10 −3 ) were obtained to achieve miniaturization and high radiation performance of antennas. Additionally, enhanced magnetization ( Ms  = 22.32 emu/g, Hc  = 55.07 Oe) as well as magnetic (tan δ μ ~10 −2 ) and dielectric tangents (tan δ ε ~10 −4 -10 −3 ) of low orders of magnitude promise outstanding operating performance in the high-frequency region.